Efeitos da vibração simultânea nas propriedades mecânicas de juntas de aço ASTM A131 soldadas pelo processo arame tubular (FCAW) - Maciel, Lucas Fernando Chagas [UNESP] (2014)
Welded joints are widely applied in industry in general, especially in the automotive, oil and gas fields, aeronautics, among others. The welding process under excitation gives good experimental results in welded joints concerning the improvement in toughness and ductility, the grain refinement, reduction of the HAZ, among others. Problems such as cracks and excessive deformations are characteristic resulting from the welding process. Thus there is a need to seek new and alternative methods for improving the quality of welded components. The objective of this work was to analyze the influence of heat treatment pre and post-heating and, especially, the application of vibrational processes Vibratory Weld Conditioning - simultaneously applied to the welding process on mechanical properties of welded joints. Plates ASTM A131 steel with identical dimensional were welded, the process Cored wire (FCAW) with shielding gas CO2. Aiming to evaluate and compare the potential benefits obtained by thermal processes, commonly used in the industry and mainly the emerging vibrational processes, five different welding conditions were randomly selected to analyze the possible influence of factors: temperature and vibration: a) Conventional; b) With pre and post-heating; c) With vibrational stress relief treatment; d) With Weld Conditioning; e) With Weld Conditioning and pre-and post-heating. The welded samples were subjected to destructive and non-destructive mechanical testing and objective measurement of earnings, the results obtained for all conditions were compared, having as reference the conventional process. The results showed significant gains as a reduction of grain size, 26.0% increase in toughness, down 11.0% from the microhardness profile of the molten zone and HAZ, among others